Electrospun fibers as drying additive in cement‐bonded alumina castables. Issue 4 (21st February 2022) - Storti, Enrico; Himcinschi, Cameliu; Neumann, Marc; Hubálková, Jana; Aneziris, Christos G.
Abstract: A simple system to produce titanium dioxide precursor fibers by electrospinning was developed. The phase composition of the fibers was analyzed before and after heat treatment by means of Raman spectroscopy. The effect of these fibers and commercial polypropylene fibers (PP) on low‐cement high‐alumina castables was evaluated. Thermogravimetry was used to investigate the drying behavior of the different batches. In addition, the permeability of sintered cylinders was compared. Elastic moduli and cold modulus of rupture were measured on sintered and on thermally shocked samples to evaluate the thermal shock resistance. As in our previous work, the results showed that the fiber addition was beneficial for the drying behavior. However, the use of electrospun fibers likely caused water retention in the samples during storage. The batch containing PP fibers showed the highest final permeability, confirmed also by mercury intrusion porosimetry and by scanning electron microscopy. Otherwise, the precursor fibers left no pore channel after sintering and the permeability of this batch was the lowest. Thermal shock had no clear impact on bulk density or open porosity for any of the batches. Due to the presence of calcium oxide from the cement binder, hibonite (CaAl 12 $_{12}$ O 19 $_{19}$ ) was detected by XRD alongside corundum in all samples.